The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
21st AIAA/CEAS Aeroacoustics Conference 2015
DOI: 10.2514/6.2015-2530
|View full text |Cite
|
Sign up to set email alerts
|

On the Adjoint-based Control of Trailing-Edge Turbulence and Noise Minimization via Porous Material

Abstract: In this paper, we present a discrete adjoint-based optimization framework to obtain the optimal distribution of the porous material over the trailing edge of a 3-D flat plate. The near-body strength of the noise source generated by the unsteady turbulent flow field is computed using a high-fidelity large-eddy simulation (LES). The acoustic signal thus generated is then propagated to the far-field using the acoustic perturbation equations (APE). The design gradients are computed using the forward and reverse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Numerical computations by Bae & Moon [15] corroborate these trends, demonstrate the ability of porous trailing edges to suppress tonal peaks in the acoustic signature, and suggest that the optimization of the porosity distribution could enable greater noise reductions (e.g. [16]). Hence, there is a potential trade-off between the acoustical benefits of porosity and its negative impact on aerodynamic performance.…”
Section: Introductionmentioning
confidence: 83%
“…Numerical computations by Bae & Moon [15] corroborate these trends, demonstrate the ability of porous trailing edges to suppress tonal peaks in the acoustic signature, and suggest that the optimization of the porosity distribution could enable greater noise reductions (e.g. [16]). Hence, there is a potential trade-off between the acoustical benefits of porosity and its negative impact on aerodynamic performance.…”
Section: Introductionmentioning
confidence: 83%
“…There are also approaches to combine the successful concept of serrated trailing edges with a porous modification [11]. In addition, there are a variety of analytical [12] and numerical studies [13][14][15][16] on porous trailing edges for noise reduction available.…”
Section: Introductionmentioning
confidence: 99%
“…Koh et al (2014) performed numerical simulations based on LES and acoustic perturbation equations (APE) on the possibility of bluntness noise reduction and found that the use of porous trailing-edges can reduce the sound pressure level at the fundamental vortex shedding frequency by 10 dB and the overall sound pressure level in the range of 3-8 dB. In addition, Zhou et al (2015) developed an LES-based discrete adjoint-based optimization framework to obtain the optimal distribution of porous materials on trailing-edge of a flat plate. More recently, Koha et al (2017) performed an LES-based computational study on the impact of porous surfaces on trailing-edge noise and showed that the implementation of porous trailing-edge can lead to a reduction of the overall sound pressure by up to 11 dB in the case of a flat plate at zero angle-of-attack.…”
Section: Introductionmentioning
confidence: 99%